Partial Reality in Local Modern Indonesia: Interethnic Marriage Preferences among Young Minangkabau Migrants in Yogyakarta - Azwar, Zainal; Armi, Mhd. Ilham; Daharis, Ade; Febria, Thomas; Aryanti, Yosi (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2024)
The preference for same-ethnic marriage in Minangkabau society is an ideal marriage pattern to preserve customs and traditions in the customary marriage system. This preference changes when juxtaposed with the tradition of migration by the Minangkabau society, which influences other preferences (interethnic) in the customary marriage system. This research explores interethnic marriage preferences among young Minangkabau migrants in Yogyakarta, an area with cross-cultural characteristics. This research hypothesises that migration influences interethnic marriage preferences among young Minangkabau migrants in Yogyakarta. This research utilises a quantitative-explanative method, and data were collected through a Likert scale questionnaire and literature on Minangkabau marriage culture and traditions. The research involved 100 single Minangkabau migrants aged 19-24 in Yogyakarta as respondents April 20, 2024, to May 6, 2024. Simple linear regression analysis and social reality construction were used as data analysis techniques. The results showed a significant influence of migration on interethnic marriage preferences among young Minangkabau migrants in Yogyakarta, with a regression coefficient of 0.307 and a significance level of 0.002 (p < 0.050). This finding indicates that an increase in the migration variable correlates with an increase in interethnic marriage preference (dependent variable). In terms of social reality, this finding shows the emergence of a partial reality in customary marriage preferences resulting from secondary socialisation internalised by young Minangkabau migrants in Yogyakarta.